2015
DOI: 10.1021/jacs.5b01555
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Diamond sp2-Defects with Unsaturated Diamondoid Oligomer Models

Abstract: Nanometer-sized doubly bonded diamondoid dimers and trimers, which may be viewed as models of diamond with surface sp(2)-defects, were prepared from corresponding ketones via a McMurry coupling and were characterized by spectroscopic and crystallographic methods. The neutral hydrocarbons and their radical cations were studied utilizing density functional theory (DFT) and ab initio (MP2) methods, which reproduce the experimental geometries and ionization potentials well. The van der Waals complexes of the oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 74 publications
2
29
0
Order By: Relevance
“…Previously, we found that DFT reproduced the experimental ionization potentials of large saturated hydrocarbons well [15 -19]. Correct descriptions of radical cations derived from 1 and 2 require taking into account both electron correlation and noncovalent interactions (NCI) [13,20] between the groups that surround the C=C bonds. Hydrocarbon 1 provides an opportunity to test the applicability of the recently developed DFT implementations to olefinic radical cations, such as 1 •+ , since its X-ray crystal structure is available [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found that DFT reproduced the experimental ionization potentials of large saturated hydrocarbons well [15 -19]. Correct descriptions of radical cations derived from 1 and 2 require taking into account both electron correlation and noncovalent interactions (NCI) [13,20] between the groups that surround the C=C bonds. Hydrocarbon 1 provides an opportunity to test the applicability of the recently developed DFT implementations to olefinic radical cations, such as 1 •+ , since its X-ray crystal structure is available [13].…”
Section: Resultsmentioning
confidence: 99%
“…Such a behavior upon ionization makes hydrocarbons 4 and 5 useful for the construction of electronic materials where the structural stiffness of the building blocks upon electron/hole transfer is critical. Derivatives of 4 and 5 may have some advantages over the diamondoid [20,39,40] derivatives previously successfully used for the construction of electron emitters and semiconductors [41 -45].…”
Section: Resultsmentioning
confidence: 99%
“…However, after thermal treatment of natural diamond, C(sp 2 )−C(sp 2 ) bonds (“graphitic islands”) tend to form in the absence of hydrogen, thus leading to electrical conduction . The question whether the electrical conduction occurs only within the sp 2 system or in combination with the sp 3 system is difficult to answer because of a large variety of different sp 2 sites, as well as functionality on the diamond surface and inner defects. Hence, it is useful to study diamond's nanometer‐sized congeners, the diamondoids, which comprise well‐defined hydrogen‐terminated nanodiamonds .…”
Section: Figurementioning
confidence: 99%
“…In fact, the diamondoid only exists as hexamantanes and pentamantanes (particle size of 0.6-0.75 nm) for the rod-shaped isomer in limited quantities from oil. Therefore, diamondoids with the desired size larger than 1 nm, in order to explore applications in nanoelectronics [1][2][3][4], for which the present of quantum limitation effects are theoretically presaged, remains problematic at the present time. This can be solved by a coupling reaction using lower diamondoids with various spacers.…”
Section: Introductionmentioning
confidence: 99%